Design and Implementation of MVB Gateway Based on Microchip - CHEN Xiao-xuan (机车电传动)
According to the current requirement of train network control system, a configurable gateway communicated between MVB and DPRAM backplane bus was designed. Software and hardware scheme of MVB gateway based on microchip were introduced in emphasis. The gateway had a configurable application programming characteristic, which met the needs of MVB gateway system and had advantages of high reliability and applicability.